Protecting Chatting Labels on Social Networks - Hemalatha, K.; Kalaivani, J. (International Journal For Research In Advanced Computer Science And Engineering, 2016)
In this business world, all information sharing delivering services are done through internet. There should be possibility for the vulnerabilities like brute force attack, cross site scripting, data breaching, SQL injection.Thus Privacy is one of the major concern. However, many solutions like black box testing tool, white box testing tool, web application security scanner etc are enforced, an attacker may still be able to infer one’s private information. Proposed model uses sensitive labels based on private key to prevent the personal information from third persons so that the users can chat securely. Furthermore, a social network like chat application will be created and the private key based sensitive labels are applied to this chatting application to analyse the performance. Also the effectiveness of the proposed technique will be analysed.